Nectarine Fruit Ripening and Quality Assessed Using the Index of Absorbance Difference (IAD) - E. Bonora; D. Stefanelli; G. Costa (International Journal of Agronomy)
Consistency of fruit quality is extremely important in horticulture. Fruit growth and quality in nectarine are affected by fruit position in the canopy, related to the tree shape. The “open shaped” training systems, such as Tatura Trellis, improve fruit growth and quality. The Index of Absorbance Difference (IAD) is a new marker that characterizes climacteric fruit during ripening. A study on fruit ripening was performed by using the IAD on nectarine to monitor fruit maturity stages of two cultivars trained as Tatura Trellis in Victoria, Australia. Fruit of cv “Summer Flare 34” (“SF34”) grown in different positions on the tree showed high ripening homogeneity. Fruit harvested at a similar ripening stage showed fruit firmness and soluble solid content homogeneity. Fruits from hand-thinned variety “Summer Flare 26” (“SF26”) were larger in size, had advanced ripening, and showed greater homogeneity. For “SF26”, a weak correlation between IAD and SSC was observed. The experiment showed that the Tatura Trellis training system is characterized by high homogeneity of nectarine fruit when coupled with a proper management of fruit density. It also confirmed that the IAD could be used as new nondestructive maturity index for nectarine fruit quality assessment in the field.